Step Right Up: Walking the Work-Life Balance Tightrope in the Circus of Higher Education - Krystal Brue; Shaun Calix; Jennifer Dennis (Academic Chairpersons Conference Proceedings, 2022)
Most professionals experience demanding obstacles when balancing on the work-life tightrope. Managing highly demanding occupational and life challenges may not come naturally. This presentation’s purpose is to examine work-life imbalance, review movements for finding harmony between work and non-work, and recommend strategies for improving work-life balance in high impact positions.
Keywords: work-life balance; work-family conflict; leadership; role conflict; spillover; work culture; work-family integration; burnout